SAW Filters on LiNbO3/SiC Heterostructure for 5G n77 and n78 Band Applications - Xu, Huiping (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2023)
The 5G communication system has experienced a substantial expansion of the spectrum, which poses higher requirements to radio frequency (RF) filters in enhancing their operating frequencies and bandwidths. To this end, this work focused on solving the filtering scheme for challenging 5G n77 and n78 bands and successfully implemented the corresponding spurious-free surface acoustic wave (SAW) filters exploiting large-coupling shear horizontal (SH) modes based on X-cut LiNbO3 (LN)/silicon carbide (SiC) heterostructure. Here, we initially investigated the suppression methods for spurious modes theoretically and experimentally and summarized an effective normalized LN thickness ( [Formula: see text] range of 0.15-0.30 for mitigating Rayleigh modes and higher order modes, as well as tilted interdigital transducers (IDT) by about 24° for eliminating transverse modes. Resonators with wavelengths ( λ) from 0.95 to [Formula: see text] were also fabricated, showing a scalable resonance from 2.48 to 4.21 GHz without any in-band ripple. Two filters completely meeting 5G n77 and n78 full bands were finally constructed, showing center frequencies ( fc) of 3763 and 3560 MHz, 3-dB fractional bandwidths (FBW) of 24.8% and 15.6%, and out-of-band (OoB) rejections of 18.7 and 28.1 dB, respectively. This work reveals that X-LN/SiC heterostructure is a promising underpinning material for SAW filters in 5G commercial applications